A marine isotope stage 13 Acheulian sequence from the Amanzi Springs Area 2 Deep Sounding excavation, Eastern Cape, South Africa. Issue 176 (March 2023) - Caruana, Matthew V.; Wilson, Coen G.; Arnold, Lee J.; Blackwood, Alexander F.; Demuro, Martina; Herries, Andy I.R.
Abstract: Renewed research at Amanzi Springs has increased resolution on the timing and technology of the Acheulian industry in South Africa. The archeology from the Area 1 spring eye has recently been dated to MIS 11 (∼404–390 ka), and analyses revealed significant technological variability when compared to other southern African Acheulian assemblages. We expand on these results in presenting new luminescence dating and technological analyses of Acheulian stone tools from three artifact-bearing surfaces exposed within the White Sands unit of the Deep Sounding excavation in the Area 2 spring eye. The two lowest surfaces (Surfaces 3 and 2) are sealed within the White Sands and dated between ∼534 to 496 ka and ∼496 to 481 ka (MIS 13), respectively. Surface 1 represents materials deflated onto an erosional surface that cut the upper part of the White Sands (∼481 ka; late MIS 13), which occurred before the deposition of younger Cutting 5 sediments (<408–<290 ka; MIS 11–8). Archaeological comparisons reveal that the older Surface 3 and 2 assemblages are predominated by unifacial and bifacial core reduction and relatively thick, cobble-reduced large cutting tools. In contrast, the younger Surface 1 assemblage is characterized by discoidal core reduction and thinner large cutting tools, mostly made from flake blanks. Typological similarities between the older Area 2 White Sands and younger Area 1 (404–390 ka; MIS 11) assemblages further suggest long-term continuity in site function. We hypothesize Amanzi Springs represent a workshop locality that Acheulian hominins repeatedly visited to access unique floral, faunal, and raw material resources from at least ∼534 to 390 ka.